Oracle exadata recipes : a problem-solution approach - Clarke, John (Apress Imprint: Apress, 2013)
Oracle Exadata Recipes takes an example-based, problem/solution approach in showing how to size, install, configure, manage, monitor, optimize, and migrate Oracle database workloads on and to the Oracle Exadata Database Machine.  Whether you're an Oracle Database administrator, Unix/Linux administrator, storage administrator, network administrator, or Oracle developer, Oracle Exadata Recipes provides effective and proven solutions to accomplish a wide variety of tasks on the Exadata Database Machine.  You can feel confident using the reliable solutions that are demonstrated in this book in your enterprise Exadata environment. Managing Oracle Exadata is unlike managing a traditional Oracle database. Oracle's Exadata Database Machine is a pre-configured engineered system comprised of hardware and software, built to deliver extreme performance for Oracle Database workloads.  Exadata delivers extreme performance by offering an optimally balanced hardware infrastructure with fast components at each layer of the engineered technology stack, as well as a unique set of Oracle software features designed to leverage the high-performing hardware infrastructure by reducing I/O demands. Let Oracle Exadata Recipes help you translate your existing Oracle Database knowledge into the exciting new growth area that is Oracle Exadata. Helps extend your Oracle Database skillset to the fast-growing, Exadata platform Presents information on managing Exadata in a helpful, example-based format Clearly explains unique Exadata software and hardware features